Differences and similarities of physical activity determinants between older adults who have and have not experienced a fall: Testing an extended health belief model. (January 2021) - Kaushal, Navin; Preissner, Christian; Charles, Kathleen; Knäuper, Bärbel
Highlights: The extended health belief model demonstrated theoretical support for cues and perceived threat. Perceived barriers predicted physical activity intention among those with fall history. Perceived benefits and cues predicted habit, regardless of fall history. Abstract: Purpose: Experiencing a fall can be a detrimental experience for older adults and may affect an individual's beliefs about participating in future physical activity (PA) behavior. The purpose of this study was to identify if determinants of PA differ between older adults who have a history of a fall (HF) and those with no history of a fall (NHF) within the Health Belief Model (HBM), expanded through the constructs of intention and habit. Materials and Methods: Participants ( N  = 667) were community-dwelling older adults who completed online measures of original HBM determinants (beliefs, barriers, self-efficacy, cues, and perceived threat variables) related to participating in PA in addition to past PA behavior and intention. Results: Novel findings include perceived barriers significantly predicted intention to participate in PA among those with a HF but not among those with NHF, and past PA behavior predicted decreased perceived threat of falling among both groups. The model also supported cues to predict physical activity habit. Conclusions: Perceived barriers (time constraints and bodily pain) deterred PA intentions among those with a HF, suggesting the importance of intervention planning to reduce/resolve these barriers for this group. Past PA was negatively associated with perceived threat of falling, which signposts the importance of providing a safe environment for older adults to engage in PA. The study also provides formative notes for interpreting and further investigating perceived threat and its antecedents (susceptibility and seriousness) in addition to cues, which generally have been omitted in previous studies that employ the HBM.